(untitled) (Swiss Medical Weekly, 2012)
QUESTIONS: P. aeruginosa infections are assumed to play a major role in the frequency of exacerbations and severity of chronic obstructive pulmonary disease (COPD). Colonisation with P. aeruginosa accelerates lung function decline, most probably due to more frequent exacerbations. In this retrospective study we aimed to determine the prevalence of colonisation with P. aeruginosa in COPD patients treated in a tertiary hospital centre. METHODS: 112 patients diagnosed with COPD testing positive for P. aeruginosa in at least one respiratory sample during the study period (2004–2008) were retrospectively analysed to estimate GOLD stage-specific prevalences, colonisation patterns, morphology and antibiotic resistance profiles of P. aeruginosa strains. RESULTS: Colonisation with P. aeruginosa was present in all COPD stages, but prevalence significantly increased with disease severity (GOLD 1: 0.7%, GOLD 2: 1.5%; GOLD 3: 1.5%; GOLD 4: 2.6%; p= 0.0003). 41% of COPD patients with P. aeruginosa-positive respiratory samples were chronic carriers, of whom 8% had mucoid strains. Carriage of a mucoid strain was associated with advanced COPD stage GOLD 4 (p= 0.01). Resistance to cephalosporins was most frequently encountered and resistance to ciprofloxacin was found in more advanced stages of COPD. CONCLUSIONS: Colonisation with P. aeruginosa was present in all COPD severity stages and colonisation with mucoid strains was more frequent in advanced COPD. Resistance to the only oral anti-pseudomonas antibiotic ciprofloxacin was more frequently encountered in severe COPD stages.